Treatment of liquefaction susceptible loose saturated clean sand with magnesium oxide - Teker, Ahmet Sinan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2021., 2021)
Static liquefaction, more risky than cyclic one in some cases, is a strain-softening case of the granular soil as sudden loss of effective stress due to quick development of pore water pressure due to static and dynamic actions. Under zero effective stress, soil strength is lost, so it behaves like a liquid. To diminish its effects, there have been proposed traditional and recently developed improvement methods including chemicals, synthethic fibers, blast densification in the aim of lowering the saturation degree, filling pore space of soil and combining soil particles together. However, these have some drawbacks such as toxicity and disturbance to ambiance, being expensive and inoperable for specific cases. As an alternative, magnesium oxide (MgO) was offered in this study due to the vast usage on medical, agricultural and constructional industries. To prevent liquefaction occurrence, the hydration mechanism of MgO, producing magnesium hydroxide precipitates was used to reduce water content and to connect soil grains. Its impacts on the compressive strength of loose, fine, fully saturated liquefiable clean sand with MgO doses of % 0.5, %1, %2, %4, %6 respectively, were investigated. Treated cylindirical soil samples were cured under 23 ⁰ C and 41% humidity for 3,7 and 14 days. Several unconfined compression tests (UCT) were made on samples under strain controlled condition. The addition of MgO after sufficient curing period removed to water content, provided to be failed earlier and made them stiffer and denser. Increase in MgO doses enhanced to unconfined compressive strength and reduced total and failure deformation capacity. Longer treatment supported to this by making them more brittle with higher Elastic Modulus, so ductility and durability was dimished. Finally, liquefiable soil was improved mechanically along with the preventetion of excessive deformation and saturation, so the possibility of liquefaction occurrence was decreased.
Keywords: Liquefaction.; Soil mechanics -- Mathematical models.; Magnesium -- Metallurgy.